SUSTAINABLE TOURISM IN TORAJA: PERSPECTIVE OF INDIGENOUS PEOPLE - Ilham Junaid (ASEAN Journal on Hospitality and Tourism, 2015)
Stakeholders in Indonesia have accepted sustainable tourism as the protection and the long use of tourism resources as well as the availability of the resources for current and the future generation. Although such concept has been recognised as a good notion for developing tourism destination, its implementation needs to be investigated. Since 1970s, Toraja has been promoted as one of the main tourism destinations of Indonesia. For this reason, Toraja was chosen as a location for qualitative fieldwork to investigate the conduct of sustainable tourism. This article provides insights about sustainability and sustainable tourism based on the perspective of indigenous people in Toraja. Participant observations and interviews to stakeholders in South Sulawesi Province, Indonesia (specifically in North Toraja and Toraja land) were utilised to obtain information about sustainable tourism. On the basis of traditional cultural practices, Torajanese believe that the way they practice culture is actually a sustainable way. The idea of sustainability links to sustainability tourism which is now being promoted by the levels of government in Indonesia.